Modelling macroinvertebrate hydraulic preferences in alpine streams. Issue 2 (31st January 2023) - Becquet, Juliette; Lamouroux, Nicolas; Forcellini, Maxence; Cauvy‐Fraunié, Sophie
Abstract: Alpine streams face rapid hydrological changes due to the effects of global warming, glacier melting, and increased water uses such as hydropower production. Defining environmental flows (e‐flow) is crucial to mitigate the ecological impacts of flow alterations. Among e‐flow assessment methods, hydraulic habitat models predict changes in habitat suitability for aquatic species under different flow scenarios. They couple hydraulic models of stream reaches with biological models relating the abundance of taxa to microhabitat hydraulics. However, there is currently no suitable biological models for alpine, often fishless streams. In this study, we develop biological models for dominant macroinvertebrate taxa in alpine streams and compare their responses to hydraulics with those published in lowland streams. Using data collected in 150 microhabitats along a gradient of shear stress within five alpine streams, we performed generalized linear mixed models relating macroinvertebrate abundance to microhabitat hydraulics (shear stress, flow velocity, Froude number and water depth). We developed biological models for 41 taxa, and observed significant microhabitat selection for shear stress (18 taxa), velocity (20), Froude number (21), and depth (11). Most of them presented consistent responses across studied alpine streams, with shear stress and velocity as the main drivers. For common taxa, shapes of macroinvertebrate responses to hydraulics were comparable with those observed in lowland streams. Nevertheless, taxa preferred slightly lower shear stress in alpine streams compared to lowland streams, probably due to high‐fine sediment and oxygen concentrations, especially for taxa feeding on autochthonous organic matter. Many (23%) abundant taxa are rheophilic in alpine streams, thereby threatened by flow reduction, including the glacial stream specialists Diamesinae and Rhithrogena delphinensis, which will be also affected by glacier retreat. Combined with hydraulic models, our biological models will facilitate more robust e‐flow assessments, thereby reducing the impacts of flow alterations on alpine aquatic ecosystems. Abstract : Half of the 41 modelled alpine taxa had significant microhabitat selection for shear stress, with consistent responses across five studied alpine streams. Most of them were rheophilic, selecting high‐shear stress microhabitats. Macroinvertebrates preferred comparable but slightly lower shear stress in alpine streams compared to lowland streams. Combined with hydraulic models, these biological models will enable assessing environmental flows in alpine regions to mitigate the impacts of flow alterations due to climate change and water uses.